Effectiveness of physiotherapy interventions for injury in ballet dancers: A systematic review - Skwiot, M.; Sliwinski, Z.; Zurawski, A.; Sliwinski, G. (PLOS ONE, 2021)
Background: The unique repetitive nature of ballet dancing, which often involves transgressing endurance limits of anatomical structures, makes dancers prone to injury. The following systematic review aims to assess the effectiveness of physiotherapy interventions in the treatment of injuries in ballet dancers. Methods: The review was performed in line with the PRISMA statement on preferred reporting items for systematic reviews and meta-analyses. Six electronic databases (PubMed, Ovid Embase, Cochrane, Medline, PEDro, Google Scholar) were queried. The study populations comprised active ballet dancers and/or ballet school attendees with acute and chronic injuries and those with persistent pain. There were no restrictions regarding age, sex, ethnicity or nationality. The Modified McMaster Critical Review Form for quantitative studies was used to assess the methodological quality of the studies reviewed in accordance with the relevant guidelines. Results: Out of the total of 687 articles subjected to the review, 10 met the inclusion criteria. Diverse physiotherapeutic interventions were described and effectiveness was assessed using different parameters and measurements. Overall, the results indicate that physiotherapy interventions in ballet dancers exert a positive effect on a number of indices, including pain, ROM and functional status. Conclusions: Due to the small amount of evidence confirming the effectiveness of physiotherapeutic interventions in ballet dancers after injuries and methodological uncertainties, it is recommended to improve the quality of prospective studies.